A Case Study of Non-Payment for Municipal Services In the Vhembe District Municipality - Schalkwyk, Andre Van (Mediterranean Journal of Social Sciences, 2012)
The aim of this study was to investigate reasons for non–payment by residents for servicesrendered by the Vhembe District Municipality. The municipalities are responsible fordelivering such services as water supply, electricity, road maintenance, refuse collection andsanitation. Multistage sampling techniques were employed. The subjects in the study weregrouped into clusters and a sample was taken from each cluster. In this case the localmunicipalities that took part in the study were selected first, followed by wards, villages andhouseholds. Households in the selected villages were selected randomly to participate inthe study. The results showed that although the municipalities were making an effort toraise revenue and send bills to the residents, some 38% of the residents were notforthcoming with payments. The reasons found in the survey for the unwillingness to payservices by residents include ignorance, poverty and simple unwillingness to pay.